SYARH AL-HADIS DAN FIQH AL-HADIS (Upaya Memahami dan Mengamalkan Hadis Nabi) - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
Basically, the embryo of the emergence of al-hadith phenomena occurs at the time of the Prophet, although the term syarh al-hadith and fiqh al-hadith have not been formally used. Syarh al-hadith at the time of the Prophet was still a unity of the hadith series itself. After the scholars were not busy with gathering and researching hadiths, they tried to study fiqh al-hadith and collect the hadiths of the Prophet which had been collected by occupying the hadith understanding in a proportional place, when the hadith was understood textually, contextually , universal, temporal and local, so that the Prophet's hadith can be understood and practiced. On the contrary, the understanding of a rigid, radical, and static hadith is the same as closing the existence of Islam which has the blessings of the era of wa-eat.